EFFECTS OF PLANT MEDIA AND FERTILIZING OF UREA FERTILIZERS ON RESULTS OF SELADA PLANTS (Lactuca sativa L.) - Nurhayati (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2017)
The result of this research is to know the influence of planting media and provision of urea fertilizer on the result of lettuce plant. The hypothesis of planting media significantly affect toward the result of lettuce plant, the urea fertilizer significantly affected toward the result of lettuce plant, and there is a real interaction between the planting media and Urea toward the result of lettuce plant. The benefits of this research is to get a combination of treatment between the planting media and fertilizer dosage of Urea the best toward the result of lettuce plant. This research was conducted at the Experimental Garden of the Faculty of Agriculture, University of Syiah Kuala in Banda Aceh, which took place from May to August 2016. The research was conducted by using a randomized block design (RAK) factorial pattern that consists of two factors: the planting media and fertilizer dosage of Urea. The treatment of the planting media consisted of four levels, namely: Factor of the planting media (comparison with soil based on the volume that is 3: 1) M1 = Soil, M2= Soil and chaff , M3 = Soil and sawdust M4= Soil and manure. Factor of Urea fertilizer that is N0= without urea fertilizer N1= 100 kg Urea/ha, N2= 200 kg Urea/ha, N3= 300 kg Urea/ha. From these two factors was obtained 16 combinations of treatments with three times of replicates thus obtainedin 48 units of experiment. The parameters was observed in leaf wide Parameter (cm2) 40 HST, Heavy of wet berangkasan (remains of agricultural plants part) (g) 40 HST, leaf heavy (g) 40 HST, Root heavy (g) 40 HST. The test result of F on variance analysis show that planting media and the provision of Urea fertilizer is very significant effect on the leaf wide of age 40 HST, heavy of berangkasan (remains of agricultural plants part) 40 HST, heavy leaf 40 HST. There is a significant interaction between planting media and the provision of Urea fertilizer to wide of leaf , the heavy of wet berangkasan , heavy of leaf, and root heavy respectively at age 40 HST. Key Words: Planting Media, Urea, Lettuce